High waist-to-height ratio and associated factors in adolescents from a city in Southern Brazil: a cross-sectional study - Bim,Mateus Augusto (2022)
ABSTRACT Objective: To verify the prevalence of abdominal obesity with the waist-to-height ratio (WHtR) and associated factors in adolescents from a city in Southern Brazil. Methods: A total of 960 adolescents (494 boys) aged 15–18 years old participated in this study. The dependent variable was WHtR; independent variables were self-reported age, economic level, sexual maturation, physical activity level, screen time, and body fat. Data were analyzed using descriptive statistics and logistic regression. Results: It was observed that 36.7% of the adolescents presented high WHtR (50.2% in girls and 23.9% in boys). Regardless of sex, adolescents with high body fat were more likely of having high WHtR (boys: Odds Ratio [OR] 29.79; 95% confidence interval [95%CI] 16.87–52.62; girls: OR 19.43; 95%CI 10.51–35.94). In girls, high WHtR was associated with age (OR 1.83; 95%CI 1.17–2.87), and in boys, with economic level (OR 2.34; 95%CI 1.01–5.45). Conclusions: One in each three adolescents has abdominal obesity. Among adolescents with high body fat, girls aged 15–16 and boys with high-income are the groups most exposed to abdominal obesity.